Impeachment as Last Resort to Safeguard Democracy? Removing the Head of Government in Different Institutional Settings - Mahir Tokatlı (Politische Vierteljahresschrift, 2023)
Democracy would essentially fail if, despite an electoral defeat, the government refused to concede office. This possibility is a~constant uncertainty that democracy has to deal with, which makes it fragile in terms of its survival. This was on full display after the 2020 U.S. presidential election, including the resulting denials by then President Trump and his followers and their attempts to have the results overturned, with the dramatic conflict culminating in the storming of the Capitol. Trust, but also mistrust, is constitutive for democratic regimes: Trust makes democracies exist, and mistrust makes them survive. Recent studies have pointed out that institutionalized mistrust has long been ignored as relevant for democracies; however, there is little if any research attention given to the most pivotal tool in terms of institutionalized mistrust, namely the vote of no confidence or the early removal of the head of government from office. In parliamentary systems, parliament can remove the head of government for political reasons, whereas presidentialism lacks this option, although impeachment provides a~way of removal on legal grounds. This article aims to prompt further reflection in comparative government on how these tools of institutionalized mistrust are defined in the context of different institutional settings and what potential risks they entail. Do the principles of trust and mistrust actually differ between the various governmental systems? Finally, does impeachment strengthen democratic principles, or is it pathological in a~sense that it might even foster autocratization?
Keywords: 320; Parliamentarism; Presidentialism; Democratic Backsliding; Mistrust; Autocracy; Parlamentarismus; Präsidentialismus; Entdemokratisierung; Misstrauen; Autokratie